Childhood Morgagni hernia: report of two cases - Kamal Nain Rattan; Jasbir Singh; Poonam Dalal (Hygeia Press di Corridori Marinella, 2017)
Morgagni diaphragmatic hernia is a rare congenital anomaly to be seen in the pediatric age group. We are reporting two cases of Morgagni hernia, which presented with non-specific symptoms and posed a diagnostic dilemma. One of the patients was 10 years old and associated with asplenia and Down's syndrome; the second case presented as isolated Morgagni hernia in an 8 month baby. The diagnosis was confirmed with radiography and computed chest tomography. Both cases were managed successfully with surgical repair of the diaphragmatic defect through trans-abdominal approach.